2008
DOI: 10.4161/cbt.7.12.6967
|View full text |Cite
|
Sign up to set email alerts
|

Activated STAT3 is a mediator and biomarker of VEGF endothelial activation

Abstract: STAT3 plays important roles in cell proliferation and survival signaling and is often constitutively activated in transformed cells.In this study, we examined STAT3 activation in endothelial cells (EC) during angiogenic activation and therapeutic angiogenesis inhibition. VEGF stimulation of cultured EC induced STAT3 phosphorylation by a VEGFR2-and Src-dependent mechanism. FGF2 but not PlGF also induced EC STAT3 activation in vitro. Activated STAT3 mediated VEGF induction of EC Bcl-2 and contributed to VEGF pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
122
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 43 publications
5
122
1
Order By: Relevance
“…However, endothelial signaling through ERK and STAT3 are known to be induced by factors other than VEGF (e.g., basic FGF) and are unlikely to be specific indicators of VEGF action. 18,25 That this may be the case in Colo-205 tumors is supported by the observation that neither p-STAT3 nor p-ERK is reduced to basal levels by VEGF Trap therapy, suggesting that factors not neutralized by this agent induce signaling through these intermediates. On the other hand, the fact that therapy reduced both p-STAT3 and p-ERK in K1735 tumor endothelial cells to levels found in normal quiescent vessels suggests that VEGF may be the predominant or sole inducer of endothelial signaling through these intermediates in these tumors.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 53%
See 2 more Smart Citations
“…However, endothelial signaling through ERK and STAT3 are known to be induced by factors other than VEGF (e.g., basic FGF) and are unlikely to be specific indicators of VEGF action. 18,25 That this may be the case in Colo-205 tumors is supported by the observation that neither p-STAT3 nor p-ERK is reduced to basal levels by VEGF Trap therapy, suggesting that factors not neutralized by this agent induce signaling through these intermediates. On the other hand, the fact that therapy reduced both p-STAT3 and p-ERK in K1735 tumor endothelial cells to levels found in normal quiescent vessels suggests that VEGF may be the predominant or sole inducer of endothelial signaling through these intermediates in these tumors.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 53%
“…Notably, the reduction in endothelial p-STAT3 occurs quickly, is significant at the first time point examined (day 3) following therapy initiation and may directly reflect inhibition of VEGF-VEGFR signaling. 18 By comparison, the reduction in p-ERK is delayed, taking 7 days in K1735 tumors and 14 days in Colo-205 tumors to become significant. This lag The tumors were excised after, 3 days, 7 days and 14 days.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…rhGH exerts its effect when rhGH binds to GHR on the tumor cell surface, and then JAK-2 is activated, which leads to serial signal cascade reaction and cell biological reactions including proliferation, differentiate, migration, inhibition of apoptosis, remodeling of cystoskeleton, and regulation of metabolic pathways. Chen et al (2008) found that pSTAT3 was a biomarker of endothelial activation that reported VEGF-VEGFR2 activity and also a key activating transcription factor on angiogenesis. The Jak-2-STAT3 pathway is one of the three classical STAT3 activating pathways, which accomplish signal transduction from extracellular to intracellular immediately.…”
Section: Discussionmentioning
confidence: 99%
“…9 In response to VEGF binding, the VEGF receptor (VEGFR) undergoes autophosphorylation and transmits metabolic signals via phosphatidylinositol 3-kinase (PI3K)/protein kinase B (also known as Akt), a signal transducer and activator of transcription 3 (STAT3), Src family kinases (SFKs), nitric oxide synthase (NOS), phospholipase C-γ (PLC-γ), mitogen-activated protein kinase (MAPK), and other signaling pathways. [10][11][12][13] Activation of these signaling cascades inhibits cell death, promotes cell cycle progression with DNA synthesis, and stimulates cell motility. These cascades also induce angiogenesis, increase vascular permeability, and enhance autocrine VEGF production.…”
mentioning
confidence: 99%